Efficiency of Project Management of the Enterprise Development under Current Economic Conditions (Economics and region, 2018)
The concept of «project» is analyzed, peculiarities of management of projects of enterprise development in modern economic conditions are analyzed, in-depth theoretical aspects on the efficiency of management of development projects, factors of increase of management efficiency of enterprise development projects are revealed.
Keywords: project; project activity; enterprise development project; project management of enterprise development